2017
DOI: 10.1111/tpj.13648
|View full text |Cite
|
Sign up to set email alerts
|

The ALDH21 gene found in lower plants and some vascular plants codes for a NADP+‐dependent succinic semialdehyde dehydrogenase

Abstract: Lower plant species including some green algae, non-vascular plants (bryophytes) as well as the oldest vascular plants (lycopods) and ferns (monilophytes) possess a unique aldehyde dehydrogenase (ALDH) gene named ALDH21, which is upregulated during dehydration. However, the gene is absent in flowering plants. Here, we show that ALDH21 from the moss Physcomitrella patens codes for a tetrameric NADP -dependent succinic semialdehyde dehydrogenase (SSALDH), which converts succinic semialdehyde, an intermediate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
(109 reference statements)
0
9
0
Order By: Relevance
“…α-Aminoadipic semialdehyde (AASAL), a substrate analog of GSAL with a 6-carbon chain, is the major substrate of ALDH7 31 and is oxidized at a rate of ~6% compared to GSAL. Succinic semialdehyde, a substrate analog of GRSAL with a 4carbon chain, is the major substrate of ALDH5 and ALDH21 32 . Succinic semialdehyde is oxidized at ~2% rate compared to GSAL.…”
Section: Substrate Specificity Of the Plant Aldh12 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…α-Aminoadipic semialdehyde (AASAL), a substrate analog of GSAL with a 6-carbon chain, is the major substrate of ALDH7 31 and is oxidized at a rate of ~6% compared to GSAL. Succinic semialdehyde, a substrate analog of GRSAL with a 4carbon chain, is the major substrate of ALDH5 and ALDH21 32 . Succinic semialdehyde is oxidized at ~2% rate compared to GSAL.…”
Section: Substrate Specificity Of the Plant Aldh12 Familymentioning
confidence: 99%
“…ZmALDH12 is NAD + -specific due to presence of the Asp226, whose negatively charged carboxylate side chain likely repels the 2'-phosphate group of NADP + . For comparison, the plant ALDH21 family members, which are NADP + -dependent, have alanine at this position 32 , suggesting that the identity of the residue at this position drives coenzyme preference. To test this hypothesis, the coenzyme preference of the ZmALDH12 D226A mutant was analyzed.…”
Section: Structural Analysis Of the Zmaldh12 Coenzyme Binding Sitementioning
confidence: 99%
“…Initial structural studies revealed ALDH7A1 forms a dimer‐of‐dimers tetramer both in crystallo and in solution . Many other ALDHs form the same tetramer, including ALDH1 , ALDH2 , ALDH5A1 , methylmalonate semialdehyde dehydrogenase , ALDH21 , 2‐aminomuconate‐6‐semialdehyde dehydrogenase , betaine aldehyde dehydrogenase , lactaldehyde dehydrogenase , indole‐3‐acetaldehyde dehydrogenase , α‐ketoglutarate‐semialdehyde dehydrogenase , propionaldehyde dehydrogenase , and salicylaldehyde dehydrogenase . Further investigation of the in‐solution oligomeric state of ALDH7A1 using analytical ultracentrifugation revealed a concentration‐dependent dimer–tetramer equilibrium with a dissociation constant ( K d ) of 16 μ m .…”
mentioning
confidence: 99%
“…EcALDH (24) and most other ALDHs (22,23), the substrate channel and the cofactor channel are always connected throughout the catalytic cycle, which is uninfluenced by the conformational changes of their catalytic residues. In the succinic semialdehyde dehydrogenase PpALDH21 from Physcomitrella patens (25)…”
Section: The Catalytic Mechanism Of Vvahgdmentioning
confidence: 99%
“…During the catalytic process, these two catalytic residues usually undergo conformational changes, which play a key role in the association/release of the cofactor/substrate/product (19)(20)(21). While the substrate channel and the cofactor channel in most ALDHs are always connected throughout the catalytic cycle (22)(23)(24), the binding of cofactor and/or substrate in some ALDHs results in the two separate channels to be connected due to the conformational change of the catalytic residue Cys (25). In addition to the catalytic residues, the conformational changes of non-catalytic residues in the substrate channel upon the binding of NAD + also induce the connection of two separate channels in the betaine aldehyde dehydrogenase from Staphylococcus aureus (21).…”
Section: Introductionmentioning
confidence: 99%